Metodología comunicativa para la difusión de la ciencia en la producción de un documental del proyecto “Ciencias Biológicas Y Sociedad” de Biotecnología de la UPS. - Reyes Bahamonde, Andrea Maritza (2013)
This current research outlines a communicative methodology for dissemination of science that permeates the contents and progress of the various fields in benefit of society in general, avoiding the restricted codes and inherent scientific languages solely to the expertise and wisdom of each branch in order to democratize the knowledge through a comprehensive language and close to concrete and colloquial uses of the general public without it falling into reductionism of content or science proposals.